Students' Perception of the Use of Duolingo Application for Speaking Skill: Persepsi Siswa terhadap Penggunaan Aplikasi Duolingo untuk Keterampilan Berbicara - Hd. Fadhilah, Izzah; Syafryadin, Syafryadin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2025)
The Duolingo mobile application facilitates flexible English language learning for pupils by including game-based aspects that enhance listening abilities. Proficiency in speaking is essential for English learners as it enables effective communication in daily interactions. The purpose of this study is to determine students' perceptions of the impact of Duolingo on their speaking skills. The objective of this research is to find out the students’ perception of the use of Duolingo application for speaking skills. This study employs a quantitative research design. This study's participants were first semester conversation class students from Bengkulu University. In this study, twenty nine students shared their perspectives. A questionnaire distributed using Google Forms was utilized to collect data. In this research, questionnaire will be use as the research instrument to know the students’ perception toward the Duolingo Application. Based on the data collected, students had a generally positive opinion of Duolingo as a useful application for improving their speaking skills. According to the data, nearly all students agree that the Duolingo software has many good effects on pupils studying English. Moreover, students feel at ease learning English and can easily understand learning materials when they utilize the Duolingo application as a learning tool.